Analysis of the Impact of Cooling Water Inlet Temperature Changes on Energy Consumption of a Water-Cooled Centrifugal Chiller in Hotel Buildings in Bali - Komarudin Komarudin; Marysca Shyntia Dewi; Robinhot Limbong; Deni Prumanto; Moh. Ali Sidik; Ari Pangesti Aji (Greenation International Journal of Engineering Science, 2026)
Global climate change and the increasing energy demand in the hospitality industry have led to greater attention toward energy efficiency and resource management. In Bali, known as one of the world's most popular tourist destinations, hotel buildings rely on cooling systems to maintain guest comfort. Water-cooled centrifugal chillers are widely used in large buildings, including hotels. This study aims to analyze the effect of variations in cooling water inlet temperature on the performance of a water-cooled centrifugal chiller in a hotel building in Bali. The research object is a Mitsubishi Heavy Industries chiller with a capacity of 250 TR using R134a refrigerant. The method used is an experimental study, focusing only on the chiller unit without considering air conditioning and cooling tower performance. The results show that increasing the cooling water inlet temperature raises condenser pressure and electrical energy consumption. At a cooling load of 72%, maintaining the inlet temperature at 27.48°C (below the maximum specification limit) can save 194.4 kWh of electrical energy per day. However, if the inlet temperature reaches 32.05°C (above specifications), energy consumption increases by 199.2 kWh per day.